High-precision, low computational-load thermal modelling for temperature control of induction hobs - Cásedas, Erik; Ramírez, Édgar (Jornada de Jóvenes Investigadores del I3A, 2024)
In this work, a computationally low-load thermal model of the induction-recipient cooking system has been developed. Using MOR (model order reduction) techniques, a reduced three-variable state model achieves an accuracy comparable to a FEM (finite element model) with thousands of nodes.